2003
DOI: 10.1002/cncr.11530
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and prognosis of patients after resection of nonsmall cell lung carcinoma measuring 2 cm or less in greatest dimension

Abstract: Die verblüffend unterschiedliche Reaktivität einfacher Komplexe des Typs [PnRhX] hängt stark von der Art und der Zahl der Trialkylphosphan‐Liganden (P) sowie den anionischen Liganden X ab: In Konkurrenzexperimenten mit Aldehyden und Methyliodid wird bei Verwendung verschiedener Komplexe selektiv eines von beiden addiert [Gl. (1) und (2)].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
57
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(61 citation statements)
references
References 28 publications
4
57
0
Order By: Relevance
“…The multivariate analyses identifi ed an older age, male sex, wedge resection, advanced stage, Noguchi classifi cation C, D, E, or F as independent prognostic factors that adversely affected the overall survival. Okada et al 8 found the pathologic stage, preoperative serum CEA level, and vascular vessel invasion to be signifi cant, independent determinants of survival in patients with a non-small cell lung carcinoma measuring 2 cm or less in diameter. Inoue et al 1 recently reported that an increased preoperative serum CEA level is an independent predictor of a poor prognosis in patients with nonsmall cell lung cancer 2 cm or less in diameter, and the rate of lymph node metastasis was signifi cantly higher in those patients.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The multivariate analyses identifi ed an older age, male sex, wedge resection, advanced stage, Noguchi classifi cation C, D, E, or F as independent prognostic factors that adversely affected the overall survival. Okada et al 8 found the pathologic stage, preoperative serum CEA level, and vascular vessel invasion to be signifi cant, independent determinants of survival in patients with a non-small cell lung carcinoma measuring 2 cm or less in diameter. Inoue et al 1 recently reported that an increased preoperative serum CEA level is an independent predictor of a poor prognosis in patients with nonsmall cell lung cancer 2 cm or less in diameter, and the rate of lymph node metastasis was signifi cantly higher in those patients.…”
Section: Discussionmentioning
confidence: 98%
“…A lobectomy is the standard surgical procedure even for small lung cancers, because some studies have demonstrated progressive disease in 10%-20% of patients with small lung cancers. 4,8 Many reports defi ne small lung cancers as having a maximum diameter of 2 cm or less, [1][2][3][4]8 and since adenocarcinoma has been reported to account for 85%-90% of small peripheral lung cancers, 1-3 in this study we restricted our analysis of small peripheral lung cancers to adenocarcinomas. Postoperatively, 89% of the patients (465) had stage IA disease, while the other 11% had progressive disease.…”
Section: Discussionmentioning
confidence: 99%
“…Anatomical resection (lobectomy or segmentectomy) and nodal dissection remain the optimal procedure for CT-detected cancers, as the risk of nodal metastases for solid lesions is in the order of 20% even below 2 cm of size, and 10% below 1 cm [55,56,57,58]. Evidence is emerging, however, that pure non-solid lesions (GGOs) of 2 cm or less have a negligible risk of metastases and may be treated by non-anatomic sublobar resections [59].…”
Section: Surgical Management and Morbidity Of Screen-detected Lung Camentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9] Most authors set "a smaller than 2 cm tumor" as one criterion for selecting segmentectomy 2-5 because T1N0M0 NSCLCs smaller than 2 cm have less frequent metastases to lymph nodes and a better prognosis after lobectomy than those of 2.1-3 cm. [10][11][12][13] In addition, most surgeons believe that a tumor smaller than 2 cm is reasonable to allow for a suffi cient surgical margin for resection of one segment. However, it has not been examined fully whether this tumor size is a reasonable cutoff size for the resection of one segment.…”
Section: Introductionmentioning
confidence: 99%